Strengthening Pancasila Student Competencies through a Mini Hydropower Project in Science Education to Support Sustainable Development Goals (SDGs) - Hikmawati Hikmawati; Muntari Muntari; Kusmiyati Kusmiyati; Irman Muliadi; Rohani Rohani; Ira Sulhiyati (Postgraduate Program, University of Mataram, 2026)
Strengthening students’ competencies, including critical thinking and creativity, is an essential part of implementing the Pancasila Student Profile within the Merdeka Curriculum. One instructional approach that can support the development of these competencies is Project-Based Learning (PjBL). This study aims to analyze the effect of implementing Project-Based Learning through a mini hydropower model project on students’ critical thinking and creativity in science learning on renewable energy topics. The study employed a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The research was conducted in the odd semester of 2025 with ninth-grade students at a junior high school in Mataram City. The sample consisted of two classes, namely an experimental class of 31 students and a control class of 29 students. The research instrument was an essay test consisting of 10 items, including 5 items to measure critical thinking and 5 items to measure creativity. The data were analyzed using descriptive statistics and one-way MANOVA. The results showed that the mean scores of students’ critical thinking and creativity in the experimental class were higher than those in the control class. The MANOVA results indicated a significance value of less than 0.05, demonstrating that the implementation of Project-Based Learning through the mini hydropower project had a significant effect on students’ critical thinking and creativity. Project-based learning in renewable energy topics not only enhances higher-order thinking skills but also supports the strengthening of Pancasila Student competencies and is relevant to achieving the Sustainable Development Goals, particularly in quality education and clean, sustainable energy.